CEO characteristics and bank performance: evidence from India. Issue 8 (17th August 2020) - Gupta, Neeraj; Mahakud, Jitendra
Abstract : Purpose: The purpose of this study is to examine the impact of chief executive officer (CEO) personal characteristics on the performance of Indian commercial banks. Additionally, it also analyses the nonlinear relationship of CEO age and CEO tenure on the bank performance. Design/methodology/approach: A balanced panel data approach has been used in this study. Particularly, the fixed effect estimation technique is used to examine the relationship between CEO characteristics and bank performance during the period 2009–2010 to 2016–2017. Findings: The authors find that professional qualification of CEOs in finance stream enhances performance. Additionally, the impact of CEO duality is found to be positive and significant on performance. Male CEOs are beneficial for bank performance. Well experienced CEOs contribute to higher performance. The results are robust across the various proxies of bank performance, and sub-samples based on ownership, size of the bank and board size. Practical implications: This study provides insights to policy regulators and policymakers who are entrusted with the appointment of the CEOs in the banks in the light of the ongoing regulatory reforms. Originality/value: This study can be considered as one of the early studies, which examines the association between CEO characteristics and bank performance from an emerging economy perspective. It also extends the existing study by considering both public and private banks operating in India.